2005
DOI: 10.1016/j.cell.2005.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Nonspecific to Specific DNA Interactions along the Substrate-Recognition Pathway of Dam Methyltransferase

Abstract: DNA methyltransferases methylate target bases within specific nucleotide sequences. Three structures are described for bacteriophage T4 DNA-adenine methyltransferase (T4Dam) in ternary complexes with partially and fully specific DNA and a methyl-donor analog. We also report the effects of substitutions in the related Escherichia coli DNA methyltransferase (EcoDam), altering residues corresponding to those involved in specific interaction with the canonical GATC target sequence in T4Dam. We have identified two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
125
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(130 citation statements)
references
References 53 publications
4
125
1
Order By: Relevance
“…It has been found that proteins contact the DNA using approximately the same binding site and orientation in all complexes (10)(11)(12)(13)(14)(15)(16)(17)(18). In nonspecific complexes, the interface between the two molecules is stabilized by electrostatic interactions between charged protein side chains and the DNA backbone (1,(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It has been found that proteins contact the DNA using approximately the same binding site and orientation in all complexes (10)(11)(12)(13)(14)(15)(16)(17)(18). In nonspecific complexes, the interface between the two molecules is stabilized by electrostatic interactions between charged protein side chains and the DNA backbone (1,(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…In nonspecific complexes, the interface between the two molecules is stabilized by electrostatic interactions between charged protein side chains and the DNA backbone (1,(9)(10)(11)(12)(13)(14)(15)(16)(17). In complexes with target DNA sites, there are also interactions between side chains and bases (10)(11)(12)(13)(14)(15)(16)(17). Strikingly, some so-called "dual-role residues" interact with the DNA backbone in nonspecific complexes and with DNA bases in specific complexes (14,15,17) or form different interactions with bases in nonspecific and specific complexes (13).…”
mentioning
confidence: 99%
See 3 more Smart Citations